2020
DOI: 10.1063/1.5124911
|View full text |Cite
|
Sign up to set email alerts
|

Tuning electronic and optical properties of free-standing Sn2Bi monolayer stabilized by hydrogenation

Abstract: In this study, we systematically investigated the structural, mechanical, electronic and optical properties of Sn2Bi monolayer, a sheet experimentally synthesized recently [PRL, 121, 126801 (2018)] which has been hydrogenated (Sn2BiH2) to stabilize free-standing form using density functional theory (DFT). For tuning the band structure and electronic properties, the mechanical strain and electric field are used. Our investigations show that in this free-standing sample, there are electron flat bands and free h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…S1 ). The same instability has also been reported for freestanding monolayer while it can be greatly stabilized by hydrogenation 34 , 35 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…S1 ). The same instability has also been reported for freestanding monolayer while it can be greatly stabilized by hydrogenation 34 , 35 .…”
Section: Resultssupporting
confidence: 78%
“…In fact, the structures represent more stability when the atoms are lighter. By comparison, one can easily realize that all the predicted monolayers are more stable than the hydrogenated Sn 2 Bi ( Sn 2 BiH 2 ), which was discussed in our previous study to have a cohesive energy of − 2.95 eV/atom 35 . Also, the Si 2 SbH 2 , Si 2 BiH 2 , Ge 2 SbH 2 , and Ge 2 BiH 2 monolayers are more stable than SiSb (− 3.50 eV/atom), SiBi (− 3.31 eV/atom), GeSb (− 3.12 eV/atom), and GeBi (− 2.98 eV/atom) binary compounds, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…Adsorption, especially by hydrogen and halogens is another well-known method for stabilizing and tuning the physical properties of nano-materials [25]. For instance, Mohebpour et al have suggested that hydrogenation stabilizes the freestanding structure of the newly onsubstrate synthesized Sn2Bi compound [26,27]. Moreover Saffari et al suggest that chlorination of CH3NH3PbI3 perovskite solar cells leads to an increased band gap and optical parameters, such as refractive index and extinction coefficient, which eventually enhances the efficiency of the solar cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the complex refractive index ( N ) is expressed as , where η­(ω) and K (ω) are the refractive index and extinction coefficient, respectively. These parameters are expressed as Furthermore, the reflectivity R (ω) and absorption coefficient α­(ω) are expressed as Additionally, the electron energy loss function L (ω) is given by the relation , and can also be expressed in terms of ε 1 (ω) and ε 2 (ω) as All these optical parameters are calculated in the interval between 0 and 20 eV for parallel ( E ∥ x ) and perpendicular ( E ∥ z ) polarization of electric field.…”
Section: Methodsmentioning
confidence: 99%